Design and Build 2D Android-based Adventure Game “Excuse Me” - Muhammad Nur Kholis; Cindy Taurusta; Ika Ratna Indra Astutik (Procedia of Engineering and Life Science, 2022)
Manners are a must for a child as basic education from an early age. Learning manners should be taught in childhood starting with an introduction to simple manners and manners. This encourages the idea to create a game that can be used as a tool in teaching etiquette for early childhood. Learning methods accompanied by play will make it easier for children to understand things easily. This educational game is entitled "excuse me" with a 2D adventure genre where a story is presented about a little boy who wants to return to his house after school, but on the way, he meets many obstacles. The little boy must pass through one after another in order to return to his home safely. This game has 5 levels and each level has different obstacles. The game framework development in this research uses the Unity 3D game engine to build android based games. The advantage of the "excuse me" game is that this game can be a more interactive and interesting learning method and can make players feel that etiquette is very important in everyday life and in the game. and the disadvantages of this game are that it cannot run on the iOS operating system, lacks levels, and has an unattractive interface. Responses from children aged 13 and over indicated that the media was "very interesting".